Exploiting pyrolysis protocols on BTDA‐TDI/MDI (P84) polyimide/nanocrystalline cellulose carbon membrane for gas separations - Norazlianie, Sazali; Wan Norharyati, Wan Salleh; A. F., Ismail; K. C., Wong; Y., Iwamoto (Wiley, 2019)
Tubular carbon membranes were fabricated by the blending of BTDA‐TDI/MDI (P84) polyimide with nanocrystalline cellulose in a controlled pyrolysis process, specifically the pyrolysis environment (He, Ar, and N2) and the thermal soak time (30–120 min). The carbon membrane layer on a tubular support is converted to carbon matrix at 800 °C with a heating rate of 3 °C min−1. The effects of these controlled pyrolysis conditions on the gas permeation properties have been investigated. The results revealed that the pyrolysis under Ar gas environment at 120 min of thermal soak time have the best gas permeation performance with the highest CO2/CH4 selectivity of 68.2 ± 3.3 and CO2 permeance of 213.6 ± 2.2 GPU.